English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

what are the answers to the following questions:
5x + 4y - 4x - 3y =
10a + 7b - 9a - 11b =
3xy + 5xy + 7x + 5y + 4x =
12pq - 5rs + 11pq - 8rs =
4a - 8b -13a - 15b =
Thanks for taking your time to answer these questions!

2007-03-05 05:04:54 · 12 answers · asked by rover45662001 3 in Science & Mathematics Mathematics

12 answers

my guess is you already know all the answers!
but just in case here are the answers anyhow.
they are also broken down so you can see the procedure in case you are serious

add like terms (all same variables)

5x + 4y - 4x - 3y = x+y
(5x-4x = x) (4y-3y = y) so answer is x+y

10a + 7b - 9a - 11b = a-4b
(10a-9a=a) (7b-11b= -4b) so answer is a-4b

3xy + 5xy + 7x + 5y + 4x = 8xy+11x+5y

12pq - 5rs + 11pq - 8rs = 23pq-13rs

4a - 8b -13a - 15b = -9a-23b

2007-03-05 05:12:17 · answer #1 · answered by Stamping Machine 2 · 0 0

Algebra help plz?
what are the answers to the following questions:
5x + 4y - 4x - 3y = x + y
10a + 7b - 9a - 11b = a -4b
3xy + 5xy + 7x + 5y + 4x = 8xy +11x +5y
12pq - 5rs + 11pq - 8rs = 23pq -13rs
4a - 8b -13a - 15b = -9a -23b

2007-03-05 13:09:45 · answer #2 · answered by ironduke8159 7 · 0 0

5x + 4y - 4x - 3y = x + y
10a + 7b - 9a - 11b = a - 4b
3xy + 5xy + 7x + 5y + 4x = 8xy +11x + 5y
12pq - 5rs + 11pq - 8rs = 23pq - 13rs
4a - 8b - 13a - 15b = - 9a - 23b

2007-03-05 13:14:06 · answer #3 · answered by ganesan 2 · 0 0

5x + 4y - 4x - 3y = x + y
10a + 7b - 9a - 11b = a - 4b
3xy + 5xy + 7x + 5y + 4x = 8xy + 11x + 5y
12pq - 5rs + 11pq - 8rs = 23pq - 13rs
4a - 8b -13a - 15b = -9a - 23b

2007-03-05 13:10:49 · answer #4 · answered by Brenmore 5 · 0 0

th first solution is 5x+4y-4x-3y=5x-4x=x,4y-3y=y.therefore it is:x+y
second solution is 10a-9a=a and 7b-11b=[-4b],therefore it is:a+[-4b] equals to a-4b.
the third is 3xy+5xy+7x+5y+4x=8xy+11x+5y.
the fourt is 12pq-5rs+11pq-8rs=23pq-13rs.
the fifth is 4a-8b-13a-15b= -9a-23b
thnx..from aishat........

2007-03-05 14:52:30 · answer #5 · answered by ayis 1 · 0 0

put the terms together that belong together.

5x - 4x + 4y - 3y
x + y

10a - 9z + 7b - 11b
a - 4b

8xy + 11x + 5y

23pq - 13rs

-9a - 23b

2007-03-05 13:15:30 · answer #6 · answered by Ray 5 · 0 0

cant be arsed to write your answers, but i'll explain easy way to do it,
bring the like terms to similar side, ie all the x terms to one side, and the y terms to the other side of the equals sign giving;
5x - 4x = 3y - 4y
and cancel terms,
same through out

2007-03-05 13:10:10 · answer #7 · answered by Anonymous · 0 0

x + y

a-4b

8xy+11x +5y

23pq -13rs

-9a -23b

2007-03-05 13:09:47 · answer #8 · answered by bignose68 4 · 0 0

i won't give you answers, but here's how to do it:
If two numbers are followed by the same variable, you can add or subtract them
examples: 8j+7j=15j, 9mb-2mb=7mb
ONLY WORKS IF VARIABLES ARE THE SAME

2007-03-05 13:12:47 · answer #9 · answered by pianoman 2 · 0 0

The first one's answer is 42...
The second one's answer is 42...
Hey, the third one's answer is 42....
This is getting weird, but the 4th one is 42, as well...
Believe it or not, the last one is 42...Bizarre!

2007-03-05 13:08:59 · answer #10 · answered by HRCostigan 1 · 0 1

fedest.com, questions and answers